Effects of Exercise on Quality of Life in Subjects with Alzheimer's Disease: Systematic Review with Meta-Analysis of Randomized Clinical Trials - Mariana Mendes; Érica Correia; Anabela Vitorino; José Rodrigues; Luís Cid; Teresa Bento; Raul Antunes; Diogo Monteiro; Nuno Couto (MDPI AG, 2023)
Alzheimer's disease is a type of dementia that progressively affects memory, thinking, and behavior. It can interfere with daily activities and lead to a decline in cognitive abilities over time. Exercise-based interventions can complement Alzheimer's disease treatment. Exercise is a valuable tool in all healthcare settings and has shown promise as an effective cognitive improvement intervention for people with cognitive impairments. This systematic review and meta-analysis aimed to analyze the effect of physical exercise on the QoL of subjects with Alzheimer's disease. A search was performed with the help of the electronic databases PubMed and Web of Science. Randomized controlled trials with exercise-based interventions were selected. Four studies met the inclusion criteria, which included interventions based on exercise. The effects were summarized using standardized mean differences (95% confidence intervals) using random-effect models. The results showed that exercise had no significant effect on the QoL of subjects with Alzheimer. Thus, the effect of exercise interventions on the QoL of patients with Alzheimer's disease is not conclusive. More research is needed about this topic and the way in which the QoL is assessed; the necessity to conduct an objective way to assess the QoL in this population is mandatory.